2019
DOI: 10.1146/annurev-genet-112618-043633
|View full text |Cite
|
Sign up to set email alerts
|

Organization of Chromosomal DNA by SMC Complexes

Abstract: Structural maintenance of chromosomes (SMC) complexes are key organizers of chromosome architecture in all kingdoms of life. Despite seemingly divergent functions, such as chromosome segregation, chromosome maintenance, sister chromatid cohesion, and mitotic chromosome compaction, it appears that these complexes function via highly conserved mechanisms and that they represent a novel class of DNA translocases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
315
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(325 citation statements)
references
References 208 publications
4
315
0
Order By: Relevance
“…The models, which also assume that MukBEF loads randomly on all chromosomal regions, explain how MukBEF clusters colocalize with the replication origin region (oriC) in wild-type cells, while MukBEF clusters localize equally with all genetic regions tested in MatP − cells. (Kakui and Uhlmann 2018;Wani et al 2018;Paul et al 2019;Yatskevich et al 2019) Is the MukBEF-organized E. coli chromosome placed randomly within a cell? Early imaging studies showed that in new-born E. coli cells that have not initiated replication, the left and right replichores are organized into separate cell halves, while oriC is at midcell (Wang et al 2006).…”
Section: Chromosome Organization In E Coli and Other Bacteriamentioning
confidence: 99%
“…The models, which also assume that MukBEF loads randomly on all chromosomal regions, explain how MukBEF clusters colocalize with the replication origin region (oriC) in wild-type cells, while MukBEF clusters localize equally with all genetic regions tested in MatP − cells. (Kakui and Uhlmann 2018;Wani et al 2018;Paul et al 2019;Yatskevich et al 2019) Is the MukBEF-organized E. coli chromosome placed randomly within a cell? Early imaging studies showed that in new-born E. coli cells that have not initiated replication, the left and right replichores are organized into separate cell halves, while oriC is at midcell (Wang et al 2006).…”
Section: Chromosome Organization In E Coli and Other Bacteriamentioning
confidence: 99%
“…Cohesin is a highly conserved chromosome-associated multi-subunit ring-shaped ATPase complex built upon subunits belonging to the structural maintenance of chromosomes (Smc) family and is important for diverse chromosome-based processes [28][29][30][31][32][33] .…”
Section: Upon Binding a Recombination Center (Rcmentioning
confidence: 99%
“…Remarkably, while CTCF degradation suppressed most CBE-based chromatin interactions, it promoted robust RC interactions with, and robust VH-to-DJH joining of, distal VHs, with patterns similar to those of "locus-contracted" primary pro-B cells. Thus, downmodulation of CTCF-bound scanning-impediment activity promotes cohesin-driven RAG-scanning across the 2.7Mb Igh locus.Cohesin is a highly conserved chromosome-associated multi-subunit ring-shaped ATPase complex built upon subunits belonging to the structural maintenance of chromosomes (Smc) family and is important for diverse chromosome-based processes [28][29][30][31][32][33] .The cohesin complex is proposed to form contact loop domains by extrusion of chromatin until reaching convergent CTCF-bound CBE anchors 2-10 . In this regard, cohesin extrudes both naked and nucleosome-containing DNA in an NIPBL-MAU2 and ATP-hydrolysisdependent manner in vitro 34,35 .…”
mentioning
confidence: 99%
“…Cohesin complex may extrude chromatin fiber individually [70] and asymmetrically [71,72], or may even use the "inchworm" model [72,73]. For clarity, we assume that cohesin loop extrusion with "two heads" as previously proposed [19].…”
Section: "Two-headed" Cohesin Loop Extrusionmentioning
confidence: 99%